S100A1: A Regulator of Striated Muscle Sarcoplasmic Reticulum Ca2+ Handling, Sarcomeric, and Mitochondrial Function. (28th March 2010) - Völkers, Mirko; Rohde, David; Goodman, Chelain; Most, Patrick
Abstract : Calcium (Ca 2 + ) signaling plays a key role in a wide range of physiological functions including control of cardiac and skeletal muscle performance. To assure a precise coordination of both temporally and spatially transduction of intracellular Ca 2 + oscillations to downstream signaling networks and target operations, Ca 2 + cycling regulation in muscle tissue is conducted by a plethora of diverse molecules. Ca 2 + S100A1 is a member of the Ca 2 + -binding S100 protein family and represents the most abundant S100 isoform in cardiac and skeletal muscle. Early studies revealed distinct expression patterns of S100A1 in healthy and diseased cardiac tissue from animal models and humans. Further elaborate investigations uncovered S100A1 protein as a basic requirement for striated muscle Ca 2 + handling integrity. S100A1 is a critical regulator of cardiomyocyte Ca 2 + cycling and contractile performance. S100A1-mediated inotropy unfolds independent and on top of β AR-stimulated contractility with unchanged β AR downstream signaling. S100A1 has further been detected at different sites within the cardiac sarcomere indicating potential roles in myofilament function. More recently, a study reported a mitochondrial location of S100A1 in cardiomyocytes. Additionally, normalizing the level of S100A1 protein by means of viral cardiac gene transfer in animal heart failure models resulted in a disrupted progression towards cardiac failure and enhanced survival. This brief review is confined to the physiological and pathophysiological relevance of S100A1 in cardiac and skeletal muscle Ca 2 + handling with a particular focus on its potential as a molecular target for future therapeutic interventions.